PENERAPAN MODEL PEMBELAJARAN QUESTIONING UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Bagas Rianto; Putri Hana Pebriana; Nurhaswinda Nurhaswinda; Sumianto Sumianto; Fadhilaturrahmi Fadhilaturrahmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This research is conducted due to the low achievement of students reading comprehension skill on the theme of healthy food material hw the body processes food in the class V SDN 005 Empat Balai On of the solusion to evercome the problem by implementing questioning model. This is a classroom action research with two child each cycle consists of two meetings. The subject of this research is grade V students, total 29 students, 16 male students and 13 famale students. The data collection teachique employed are documentation, observasion, and tes. While technical data analysis uses quantitative and qualitative data analysis. Based on the result of data analysis, it can be seen that the student’s classical completeness in the pre action was 37,93%, then in the first cycle the first meeting in creased to 55,17%, the first cycle the second meeting increased to 68,98%. Furthermore, cycle two meeting one increased to 75,86% and cycle two meeting two increased to 82,76%.. It can be inferred concluded that the application of the questioning model can improve students reading comprehension skills on the reading text material for grade V SDN 005 Empat Balai